Praktik Leasing di Indonesia dalam Tinjauan Hukum Islam - Azwarfajri Azwarfajri; Ainun Najib (Program Pascasarjana Universitas Ibrahimy, 2021)
The development of leasing in Indonesia was in line with the development of banking, both bank and non-bank institutions. This development was certainly inseparable from the demands and needs of the community that they cannot fulfil on their own. The emerging financing institutions carry out activities in the form of providing funds or capital goods by not withdrawing funds directly from the public. The existence of leasing as a means for developing investment financing and empowering the community's economy was still considered to have several problems. Although the practice of leasing in Islamic law was equated with the contract of ijarah vomitiyah bi at-tamlik, in practice in Indonesia the process of leasing agreement was considered fasid, because there was an element of ambiguity in the contract agreement as regulated in the provisions of multi-aqad agreements, both conventional and sharia. This research will discuss the practice of financing in the community categorized as leasing under the provisions of applicable law and a review of Islamic law on the implementation of such leasing.